Effectiveness and safety of electroacupuncture in female overactive bladder: a randomized controlled trial investigating sacral and tibial nerve modulation - Tan, Zilong; Ding, Mengdi; Li, Junru; Luo, Ran; Shen, Jianwu (Frontiers in Medicine, 2025)
BackgroundOveractive bladder (OAB) is a common condition in women, affecting quality of life with symptoms like urgency, frequency, and nocturia. Current treatments, such as antimuscarinic drugs, have side effects that limit their effectiveness. Electroacupuncture (EA) shows promise as an alternative, but its mechanisms and effectiveness for OAB are not fully understood.ObjectiveThis blinded, randomized controlled trial aimed to evaluate the efficacy and safety of electroacupuncture as a therapeutic intervention for female patients with OAB and to explore potential mechanisms involving the sacral and posterior tibial nerves.MethodsSixty-eight female OAB patients were stratified and randomized into two groups. One group received EA treatment at BL33 and SP6 acupoints three times weekly for 4 weeks, while the control group received tolterodine, a standard antimuscarinic medication. Outcome measures included urgency symptoms, Overactive Bladder Symptom Score (OABSS), and quality of life at 2 and 4 weeks post-treatment, as well as at a 3-month follow-up. Safety and acceptance of EA were also assessed. Additionally, urinary cytokine levels were analyzed to investigate the neurobiological impact of the treatments.ResultsNo significant baseline differences were observed between the groups. At 2 weeks, EA significantly improved quality of life scores (p = 0.002), and by 4 weeks, both groups showed improvements in urgency symptoms and quality of life (p < 0.05), with no significant difference in OABSS (p = 0.081). The EA group demonstrated a significantly higher overall effective rate (88.6%) compared to the medication group (48.5%) (p = 0.002). Safety assessments indicated high acceptance and minimal discomfort with EA, while post-treatment urinary cytokine analysis revealed significant changes in BDNF levels, suggesting a neurobiological effect of EA.ConclusionElectroacupuncture at BL33 and SP6 is a promising, well-tolerated, and effective intervention for OAB, supporting its integration into treatment paradigms. Further research is needed to optimize its clinical application.Clinical trial registrationclinicaltrials.gov, identifier ChiCTR-1900021372.